Mô phỏng đụng độ trong mạng cục bộ Ethernet - Loi, Phi Manh (Journal of Computer Science and Cybernetics, 2018)
As a test equipment in the Local area network working on CSMA/ CD kine access prineip, the collision generator have an important position in the system test. Using this generator the system engineer can greatly simplify his work in software design.